Secretion of immunoregulatory cytokines by mesenchymal stem cells - Kyurkchiev, Dobroslav (Baishideng Publishing Group Inc, 2014)
According to the minimal criteria of the International Society of Cellular Therapy, mesenchymal stem cells (MSCs) are a population of undifferentiated cells defined by their ability to adhere to plastic surfaces when cultured under standard conditions, express a certain panel of phenotypic markers and can differentiate into osteogenic, chondrogenic and adipogenic lineages when cultured in specific inducing media. In parallel with their major role as undifferentiated cell reserves, MSCs have immunomodulatory functions which are exerted by direct cell-to-cell contacts, secretion of cytokines and/or by a combination of both mechanisms. There are no convincing data about a principal difference in the profile of cytokines secreted by MSCs isolated from different tissue sources, although some papers report some quantitative but not qualitative differences in cytokine secretion. The present review focuses on the basic cytokines secreted by MSCs as described in the literature by which the MSCs exert immunodulatory effects. It should be pointed out that MSCs themselves are objects of cytokine regulation. Hypothetical mechanisms by which the MSCs exert their immunoregulatory effects are also discussed in this review. These mechanisms may either influence the target immune cells directly or indirectly by affecting the activities of predominantly dendritic cells. Chemokines are also discussed as participants in this process by recruiting cells of the immune systems and thus making them targets of immunosuppression. This review aims to present and discuss the published data and the personal experience of the authors regarding cytokines secreted by MSCs and their effects on the cells of the immune system.